Compound Semiconductors. Issue 5 (21st May 2013) - Krishna, Sanjay; Plis, Elena; Bhattacharya, Pallab; Huffaker, Diana; Krishna, Sanjay; Plis, Elena
Abstract The present issue of physica status solidi contains papers presented at the 39th International Symposium on Compound Semiconductors (ISCS 2012) held in Santa Barbara on the UCSB campus, August 27–30, 2012. ISCS 2012 was colocated with the 24th International Conference on Indium Phosphide and Related Materials (IPRM 2012) during Compound Semiconductor Week (CSW 2012). CSW 2012 was kicked‐off with a joint plenary session. The four distinguished plenary speakers and the titles of their talks were William Deal, THz Integrated Circuits; John Geisz, III–V Semiconductors for High‐efficiency Multijunction Photovoltaics; Andrew Shields, Semiconductor Devices for Quantum Information Applications; Marc A. Taubenblatt, Optical Interconnects for Computer‐com. The opening session was followed by invited talks, contributed oral presentations, and poster presentations in both ISCS and IPRM. Also included in the technical program were two short courses and a rump session organized by IPRM. The week also included an awards session, an excursion to downtown Santa Barbara with wine tasting and the conference barbeque on Goleta beach. We extend our sincere thanks and appreciation to members of the Program Committees for their tireless efforts in assembling a high quality technical program and to members of the International Steering Committees and the UCSB Committee on Local Arrangements for their help. We also thank the exhibitors for their participation and support and gratefully acknowledge the support provided by the Office of Naval Research. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)